If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = 2x + 6 + 3x Reorder the terms: 4 = 6 + 2x + 3x Combine like terms: 2x + 3x = 5x 4 = 6 + 5x Solving 4 = 6 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 4 + -5x = 6 + 5x + -5x Combine like terms: 5x + -5x = 0 4 + -5x = 6 + 0 4 + -5x = 6 Add '-4' to each side of the equation. 4 + -4 + -5x = 6 + -4 Combine like terms: 4 + -4 = 0 0 + -5x = 6 + -4 -5x = 6 + -4 Combine like terms: 6 + -4 = 2 -5x = 2 Divide each side by '-5'. x = -0.4 Simplifying x = -0.4
| 6(-35/36)+2 | | 2x=12.4 | | 4x+(3x+40)=180 | | a^7+6a^6d-7a^5b^2= | | 3x=y+14 | | 4x+(3x+40)=90 | | -58-8x=10x+19 | | 5x+12=6x-10 | | 3x+10=82-62 | | a^5+6a^4b-7a^3b^2= | | 6-3(2w+4)=(8-w) | | 3x+1/2=5/6 | | (5x-9)/x=8y | | Qs=10+3p | | 8y=5x/x-9/x | | 2/9x100 | | 4a+2b=16 | | 2x+21=9x-56 | | 5+2k=18 | | 6(-35/37)+2 | | m-3m+3m=11 | | 6(6z+2)+z=-23 | | 4/2^-2 | | e^2x=2.5 | | M^2+8m-16=0 | | x^3-5x^2+4x+6=0 | | 1/4^-3 | | 6X^6-18x^5+36x^4= | | -3r=21 | | x/6-4=6 | | r=-7 | | x^3+-5x^2+4x+6=0 |